Pendampingan Pembacaan Iqro’ dan Al-Qur’an dengan Tajwid untuk Meningkatkan Kualitas Bacaan Siswa-Siswi di MI Darul Ulum Kota Palangka Raya - Norhidayah Norhidayah; Sri Hidayati; Sukirman Sukirman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of writing this service article is to provide assistance to students in reading iqro and al-qur'an in order to improve the quality of reading in accordance with the rules of tajweed science. MI Darul Ulum Kota Palangka Raya has its own challenges, namely that there are still many students who are not fluent in reading iqro and al-qur'an so they need intense teaching. Assistance in reading iqro and al-qur'an with tajweed to improve the quality of students' reading with the Asset Based Community Development (ABCD) method is a suitable solution in order to develop the assets that each student already has. This service aims to explore the effectiveness of such assistance in the context of improving the quality of students' reading in reading Iqro' and Al-Qur'an. The ABCD method is used as a framework, where this approach emphasizes the use of local potential and existing resources in the community to overcome problems. The assistance was carried out by involving one of the teachers and also several students who were not fluent in reciting the Quran to support the assistance activities of reading Iqro' and Al-Qur'an with tajweed. The results of the service showed that the assistance of reading Iqro and Al-Qur'an with tajweed was able to improve the quality of MI Darul Ulum Palangka Raya students. The existence of this service program helps teachers to be more intense in teaching students to read Iqro' and the Qur'an, and makes students more eager to continue learning regularly every day to develop the quality of their reading in reading Iqro' and also the Qur'an. With the ABCD method, Iqro' and Al-Qur'an reading assistance has opened opportunities for teachers and students in improving the quality of religious learning, as well as empowering local communities in facing educational challenges.